2023
DOI: 10.1021/acs.inorgchem.3c02008
|View full text |Cite
|
Sign up to set email alerts
|

Better Covalent Connection in a Molecular Triad Enables More Efficient Photochemical Energy Storage

Abstract: Numerous studies have explored the kinetics of light-induced charge separation and thermal charge recombination in donor–acceptor compounds, but quantum efficiencies have rarely been investigated. Here, we report on two essentially isomeric molecular triads, both comprising a π-extended tetrathiafulvalene (ExTTF) donor, a ruthenium­(II)-based photosensitizer, and a naphthalene diimide (NDI) acceptor. The key difference between the two triads is how the NDI acceptor is connected. Linkage at the NDI core provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 103 publications
2
0
0
Order By: Relevance
“…In the meantime, Wenger and co-workers reported a detailed study on the oxidative quenching of a similar Ru(dqp) 2 -based assembly with a NDI acceptor, which showed only 6% of charge separation. 24 Their findings corroborate our result and general interpretation, and thus, a more detailed study is in due course but beyond the scope of this study. Nonetheless, the much higher quenching extent of the triad with respect to the dyads indicates the formation of a charge-separated state.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In the meantime, Wenger and co-workers reported a detailed study on the oxidative quenching of a similar Ru(dqp) 2 -based assembly with a NDI acceptor, which showed only 6% of charge separation. 24 Their findings corroborate our result and general interpretation, and thus, a more detailed study is in due course but beyond the scope of this study. Nonetheless, the much higher quenching extent of the triad with respect to the dyads indicates the formation of a charge-separated state.…”
Section: Resultssupporting
confidence: 90%
“…Notably, previous studies on polymer-bound NDI acceptors showed efficient charge separation, but the assemblies differ markedly in terms of the linkage motif, the mutual spatial orientations, the number of potential acceptor sites and minimum distance between the closest acceptor site and the Ru core due to conformational freedom of the polymer backbone. In the meantime, Wenger and co-workers reported a detailed study on the oxidative quenching of a similar Ru­(dqp) 2 -based assembly with a NDI acceptor, which showed only 6% of charge separation . Their findings corroborate our result and general interpretation, and thus, a more detailed study is in due course but beyond the scope of this study.…”
Section: Resultssupporting
confidence: 89%